Analisis Pilihan Rasional Mahasiswa Universitas Negeri Padang Menonton Konten Pornografi pada Tiktok - Muhammad Algifari; Mira Hasti Hasmira (Jurnal Perspektif, 2023)
This study aims to explain the rational choice analysis of Padang State University students in watching pornographic content found on the Tiktok application. This is interesting to study because of the various types of content available on Tiktok, pornographic content is one of the most popular content by Padang State University students while playing the Tiktok application. The theory used to analyze this research is rational choice theory by James S. Coleman. The research method uses a qualitative approach with a case study research type. Data collection by means of observation, interviews and documentation studies. The selection of informants used snowball and purposive sampling with a total of 15 informants, with the criteria of Padang State University students who are still active in college, Padang State University student friends who also play Tiktok, and students who have played Tiktok for more than 1 year. The results of the study show that there are several factors that influence students in watching pornographic content on the Tiktok application, these factors consist of, including: first, internal factors. Internal factors are factors that come from within the students themselves, for example, such as the emergence of curiosity to see pornographic content on the Tiktok application. Second, external factors. External factors are factors that come from outside the student's self, for example the influence of peers who invite or send pornographic content to their friends, then the Tiktok algorithm which becomes the Tiktok system for displaying content that will be displayed to its users, as well as the Tiktok application which is easy to use.